(Re)conceptualization of Memory in Ukraine after the Revolution of Dignity - Fedinec Csilla; Фединець Чілла; Csernicsko Istvan; Csernicskó István; Черничко Степан (Silesian University in Opava, Faculty of Public Policies, 2017)
Abstract. In Ukraine, having arrived at a critical stage of its history, three areas can be highlighted at the level of legislation during the struggle for the way forward since the end of 2013: the language issue, the constitutional process, and the efforts to eliminate the Soviet legacy. The subject of our analysis is the four laws belonging to the 2015 legislative package on decommunization, with an outlook to the broader context, as well. The four laws in question decide about who are heroes and who are enemies in history; what Ukraine’s relationship is with World War II, as well as with the Communist and Nazi regimes. The laws point out firmly and excluding any further debate the primacy of the country’s independence over all else, and the protection of the ideal of independence by any means concerning both the past and the present. The laws prescribe impeachment as a sanction for denying their contents. This story – hot memory influenced by politics – will be summarized for the period of 2015–2016.
https://cep.slu.cz/magno/cep/2017/mn1.php?l=en
Keywords: Ukraine; "decommunization package"; national memory; identity crises; democratic values